BETWEEN RISKS AND PREVENTION: YOUNG UNIVERSITY HEALTH STUDENTS' SOCIAL REPRESENTATIONS ABOUT THE HUMAN PAPILLOMAVIRUS - Queiroz, Ana Beatriz Azevedo; Carvalho, Ana Luiza de Oliveira; Silva, Joyce Cristina Meireles da; Bezerra, Juliana da Fonsêca; Pinto, Carina Bulcão; Santos, Gabriela Silva dos (Cogitare Enfermagem, 2022)
Objective: to identify the social representations of young university students in the health area about the Human Papillomavirus and to analyze how they develop risk factors and prevention strategies against this infection. Method: an exploratory and descriptive study based on the Theory of Social Representations and carried out from July 2018 to July 2020 using the Free Word Association Test with 200 students from 14 health areas at a public university in Rio de Janeiro, Brazil. The data were analyzed by means of Correspondence Factor Analysis using the Tri-Deux 5.2 program. Results: the university students' representations vary according to gender and sexual orientation. However, they only direct responsibility for prevention of the disease to women. Conclusion: identifying young people's representations about the Human Papillomavirus contributes so that Nursing can devise strategies to face it through the training of these future professionals.